Artemisinin Derivatives and Synthetic Trioxane Trigger Apoptotic Cell Death in Asexual Stages of Plasmodium - Gunjan, Sarika; Sharma, Tanuj; Yadav, Kanchan; Chauhan, Bhavana S.; Singh, Sunil K.; Siddiqi, Mohammad I.; Tripathi, Renu (Frontiers in Cellular and Infection Microbiology, 2018)
Malaria is one of the major causes of morbidity and mortality in developing countries especially in Africa. Although over the last fifteen years, prevalence of malaria became reduced by over half but developing resistance against artemisinin derivatives and its combinations, which are only ray of hope to treat resistant malaria set back the control efforts and the key hindrance to achieve the goal of malaria elimination till 2030. In spite these artemisinins are precious antimalarials, their action mechanism is yet to be fully understood. Reactive oxygen species (ROS) produces by cleavage of endoperoxide bridge of artemisinin derivative are known to be its antimalarial efficacy. Since ROS could induce apoptosis, in present study we had investigated the effect of artemisinin derivatives on apoptotic pathway of malaria parasite and its survival. We have studied the effect of α/β arteether, artesunate and a synthetic 1, 2, 4 trioxane on apoptotic machinery of asexual blood stages of Plasmodium falciparum 3D7. To assess the effect of artemisinin derivatives on apoptotic machinery of parasite, we have measured mitochondria membrane potential, caspase activity and DNA fragmentation. Apart from this, we have also measured generation of reactive oxygen species in artemisinin treated parasite. Results have shown that these artemisinin derivatives and 1,2,4 trioxane give rise the features of apoptotic cell death including depolarization of mitochondrial outer membrane potential, activation of caspase like enzyme and DNA fragmentation. Monitoring of oxidative burst in treated and untreated parasites has revealed that cleavage of peroxide bridge of artemisinin derivatives and 1,2,4 trioxane generate reactive oxygen species which depolarize mitochondrial membrane potential and make it permeable which further followed by downstream events of apoptotic cell death. These finding suggest that artemisinin derivatives and synthetic trioxane induce apoptosis in erythrocytic stage of malaria parasite; Plasmodium falciparum.